Actualization Of Catholic Religious Education Values In Realizing Religious Tolerance Among Catholic Students In The City Of Sorong - Eduardus Sepryanto Nadur; Mery Matande; Roi Stefanus Salan Nele (Eduvest - Journal of Universal Studies, 2024)
The type of this research is qualitative-descriptive. Thirty schools located in the city of Sorong, covering primary to secondary education levels, were selected as the research locations. Approximately 35 Catholic religion teachers participated as research informants. Interview, observation, and documentation study techniques were used as methods to collect data. This research aims to examine the implementation and effectiveness of the Catholic Religious Education (PAK) learning process in schools. The researchers then attempted to explore further how schools continuously strive to improve the quality of implementing Catholic Religious Education in schools for fostering attitudes and behaviors of religious tolerance in schools. Through the Catholic Religious Education learning model, students are able to: First, adopt a critical attitude towards various issues related to racism, fanaticism, ethnicity, and repressive aspects in society. Second, conduct studies on various issues stemming from diverse perspectives of religions and other beliefs, thereby fostering awareness of cultural diversity and peace. Third, develop cooperative learning skills and decision-making skills so that students are ready to become good citizens in terms of social and democratic aspects as well as tolerant.